Diagnosis and Treatment of Gout Arthritis - Reagan, Muhammad (HM Publisher, 2022)
Gout is a heterogeneous, often familial, metabolic disease associated with abnormal deposits of uric acid in tissues and initially characterized by recurrent acute arthritis, usually monoarticular, and later by chronic deforming arthritis. Urate deposition occurs when serum uric acid is saturated (that is, at greater than 6.8 mg/dL [404.5 mcmol/L]). Hyperuricemia is caused by excess or underexcretion of uric acid, sometimes both. The disease is especially common in the Pacific islands, for example, the Philippines and Samoa. Acute gouty arthritis is sudden in onset and often occurs at night. It may develop without a clear precipitating cause or may follow a rapid increase or decrease in serum urate levels. Common precipitants are excess alcohol (especially beer), changes in medications that affect urate metabolism, and, in hospitalized patients, fasting before medical procedures. This literature review presents gout arthritis, symptoms and signs in general to the prognosis of this disease.